Trends in Al-Qur’an-Integrated Mathematics Research: A Bibliometric Analysis of 2014-2024 - Alghar, Muhammad Zia; Rizqiyah, Anisatu (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to provide an overview of mathematics research integrated with the Al-Qur’an from 2014 to 2024. The method used in this research is bibliometric analysis. The data collected are 108 articles with keywords, abstracts, and research titles containing math and Al-Qur’an. The data was obtained from the Google Scholar database downloaded through the Publish or Perish (POP) application. Then, the data was checked, sorted, analyzed, and visualized with the help of Ms. Excel and VOSViewer applications. The results showed that the trend of research related to Al-Qur’an-integrated mathematics has increased from 2014 to 2024. In addition, this study maps various Al-Qur’an-integrated mathematics research based on the type of publication, publication period, researcher productivity, type of research, integration model, mathematics material, and themes from the Al-Qur’an used. This research is useful in providing mapping, providing an overview of current trends, and providing interrelationships between topics in integrated mathematics research.